Analisis Kausalitas: Pengaruh Positif FDI terhadap Pertumbuhan Ekonomi di Provinsi Maluku, 1971-2007 - Tono Mahmudin (EKO-REGIONAL, 2010)
This study investigates the relationship between foreign direct investments (FDI) and economic growth in Maluku. The relationship on that variables is very important because Maluku has to optimize the economic growth in order to save from crisis. Econometrics technique Granger causality is used to estimate the short and long run relationship of these variables with the co-integration analysis as suggested by Johansen. This research is using time series data, 1971 to 2007. The finally results is the one-way relationship between foreign direct investment (FDI) and economic growth which FD has positive impact toward economic growth. Keywords: foreign direct investment (FDI), economic growth, Granger causality